Osteoarthritis of the temporomandibularjoint (Mustansiria Dental Journal, 2024)
Osteoarthritis (OA) is a degenerativejoint disease marked by progressive lossof articular cartilage and damage of bony components. The clinical features include;joint pain, crepitus and limitation of movement. The exact cause of OA is unknownhowever some authors consider it as a multifaetorial disease. The age and over usageare the most common tactors, in addition to race and sex. ln case oftemporomandibular joint(TMJ), traumatic occlusion, and over load caused byparafunctions are additional factors. The purpose ofthis investigation was to study theTMJ) arthropathy among a group of Iraqi patients previously diagnosed as having(.OAOne hundred patients with OA are used in this study. They were examined.clinically and radiographically for effects of systemic OA on TMJResults of the study revealed that 39% of patients with OA have TMJ lesions ofdifferent degrees ranged between osteophytes, diminusion of joint space and bone.distruction ofglenoid fossa and head of condyleDental management of temporomandibular joints affected with OA usuallyaim to suppress the active disease, preserve functions, prevent deformity and relievepain. Early detection of the disease and early commencement of management greatly ireduce joint destruction and improve prognosis. Results of this study indicated thatl1% of patients had only TMJ lesions, with no other joints lesions. Because ofdifficulty of interpretation of TMJ radiographs we suggest criteria for radiographicdiagnosis of osteoarthritis ofthe TMJ